Price Volatility and Cereal Food Security in Tunisia: Determining the Critical Threshold of Cereal Price Volatility Using the Threshold Model - Gannoun, Ibtissem; Liouane, Naoufel; Jammali, Dorsaf (Business and Economic Research, 2024)
This study examines the substantial impact of grain price volatility on food security in Tunisia, a nation heavily reliant on cereal consumption. Employing Hansen's (1999) threshold model, we pinpoint the precise level of price volatility that poses a significant threat to cereal food security in Tunisia. A novel application of this methodology, our analysis, spanning 1991-2021, focuses on cereals, constituting over 50% of Tunisia's food imports. The threshold model identifies a critical volatility threshold of 4.65%. Beyond this point, food security is significantly compromised. This finding underscores the study's capacity to quantify the precise level of grain price volatility that exacerbates food security risks in Tunisia. To mitigate these risks, policymakers should prioritize price stabilization measures, enhance risk management and storage mechanisms, and develop targeted adaptation strategies for vulnerable populations. These actions will bolster the resilience of the Tunisian food system.